Perancangan Web E-Commerce Dengan Menggunakan Pendekatan WISDM - Indra Setiadi Ramadhan; M Izman Herdiansyah (STMIK Budi Darma, 2022)
Cahaya Konveksi Shop is an industry that manufactures apparel, such as t-shirts, polo shirts, shirts, training pants, jackets, and so on. On a normal day the Cahaya Konveksit Shop can produce 100-500 t-shirts in a day, while at the beginning of the semester or new student registration at school, Cahaya Konveksi Shop can produce 500-1000 t-shirts in a day because many schools make uniform t-shirts for students new. The problem found from this store is that there are many competitors who have just started the same business as the Cahaya Konveksi Shop, which has an impact on reducing the number of orders. With this situation, stores are required to make innovations in service to consumers. The application of web-based E-Commerce is one solution to this problem. In the system there is also the WISDM Method (Web Information System Development Methodology) which is a method in system development that aims to make a program quickly and gradually so that it can be immediately evaluated by the user. In addition, WISDM also makes the process of developing information systems faster and easier, especially when user needs are difficult to identify. With this website, Cahaya Konveksi Shop has superior value that its competitors do not yet have, by adding features that can make it easier for sellers and buyers to do business. The result of this research is to create a web-based e-commerce information system at the Cahaya Konveksi Store